Sistematización de las experiencias en restauración desarrolladas por la fundación Naturaleza y Cultura Internacional en la reserva Jamboé, provincia de Zamora Chinchipe. - Masache Novillo, Yulisa Bertila (2025)
Ecological restoration helps nature recover when it is damaged. It makes ecosystems better, but sometimes they cannot be the same as before because of nature and other problems. This process is difficult because people do not always know how to do it, and also because of social, political, and economic problems. In Ecuador, people try to help nature grow again, especially in Zamora Chinchipe. In this place, mining, cutting trees, and building cities hurt the environment a lot. Because of this, an organization called Naturaleza y Cultura Internacional (NCI) started a project in the Jamboé Reserve. But this project does not have many documents about what they did. This study wants to organize information about the project to help future work. People talked to families and workers to understand if the project worked well or not. They found good things and problems. The study made plans to help nature in a way that is good for the economy too. The project was complete and included local people and schools. The Body Shop and WLT gave money to help. It had three steps and helped the economy by growing a plant called Bixa orellana, which people can sell. This successful project shows that people should keep working together, think about money for the future, and check the results for a long time to make sure nature gets better.